PARAMETRIC DESIGN IN CONTEMPORARY ARCHITECTURE: ENHANCING FORM AND FUNCTION THROUGH COMPUTATIONAL TOOLS - Hamidova Mohigul Hayotovna; Vohidov Shakhzod Kenjayevich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: Parametric design has revolutionized the field of architecture by enabling dynamic, responsive, and highly optimized structures. This article explores the theoretical foundations and practical applications of parametric design, emphasizing how computational tools such as Grasshopper, Rhino, and Autodesk Revit are used to generate innovative architectural forms. The research investigates global case studies and examines the potential integration of parametric techniques in emerging markets such as Uzbekistan. Findings suggest that parametric architecture not only enhances aesthetic complexity but also improves environmental performance, structural efficiency, and user adaptability.